A 0.25-V calibration-less inverter-based OTA for low-frequency Gm-C applications. (January 2019) - Braga, Rodrigo A.S.; Ferreira, Luís H.C.; Coletta, Gustavo D.; Dutra, Odilon O.
Abstract: This paper presents a calibration-less inverter-based operational transconductance amplifier (OTA) built with intrinsically matched CMOS inverters, therefore, dispensing any kind of calibration circuit. In addition, the circuit is implemented in IBM 130-nm CMOS processes using non-uniformly doped MOS transistors and is specially designed to suit low-frequency G m -C applications such as biomedical applications. The intrinsically matched CMOS inverters design relies on the utilization of the distributed layout of halo-implanted MOS transistors operating in weak inversion. In this work we demonstrate that this technique stabilizes the switching point voltage of the CMOS inverter, reducing its statistical variation, besides allowing gain enhancement and its adjustment, which is desirable for the G m -C design. Based on the original topology proposed by Bram Nauta (and its derivative works), focusing on the tunability of VHF filters, we adapt this topology for constant G m applications. Moreover, the proposed circuit features a 2.46- μ S transconductance when supplied with 0.25-V, dissipates 55-nW during operation making it suitable to low-power applications.